ANALYSIS OF ECODIESEL CHARACTERISTICS WITH A VEGETABLE-BASED OIL ESTER FOR THE TRANSPORTATION SECTOR - Balo, Figen; Sua, Lutfu S. (American Institute of Physics Inc., 2021)
[Abstract Not Available]
Keywords: Ecodiesel; Transportation sector; Vegetable based oil; Petroleum transportation